Composition range and electrical properties of the morphotropic phase boundary in Bi0.5(Na0.80K0.20)0.5TiO3-(Ba0.7Sr0.3)TiO3 system - Pharatree Jaita (2018)
The lead-free piezoelectric ceramic binary system of (1-x)Bi0.5(Na0.80K0.20)0.5TiO3-x(Ba0.7Sr0.3)TiO3 or (1-x) BNKT-xBST (with x ranging from 0.05 to 0.15 mol fraction) near the morphotropic phase boundary (MPB) has been investigated. The ceramics were synthesized by a conventional mixed-oxide method and sintered at 1125°C for 2 h. All BNKT-BST samples had relative density higher than 98% of their theoretical values. X-ray diffraction patterns showed that all compositions had a pure perovskite structure and BST effectively diffused into the BNKT lattice during sintering to form a solid solution. Crystal structure changed from rhombohedral-rich phase to tetragonal-rich phase with increasing BST content. Because of such MPB-like behavior, the highest dielectric (Tc = 325°C, eopenr = 1827, tan δ = 0.0823) and piezoelectric performances (d33 = 225 pC/N) were obtained in the BNKT-0.11BST sample. © 2013 The Korean Institute of Metals and Materials and Springer Science+Business Media Dordrecht.